Ethnicity, Pottery, and the Hyksos at Tell El-Maskhuta in the Egyptian Delta - Redmount, Carol Ann 1952- (1995)
Once a mysterious presence in Egyptian history, the Hyksos (ca. 1663-1555 BCE) offer a fortunate case where a particular material culture can be associated with a specific people. Pottery unearthed at Tell el-Dab˓a and Tell el-Maskhuta provides complementary evidence for defining Hyksos material culture. While exhibiting a dominant Middle Bronze Age Canaanite heritage, these ceramics show that the Hyksos produced a culture that joined Canaanite and Egyptian traditions with the addition of locally developed traits.